ILWIS version 1.3 ....an Interesting and Affordable Tool - Abdul Rahman, Alias (Fakulti Ukur dan Harta Tanah, 1994)
It is a PC based low cost GIS and Remote Sensing software. A dual monitor system, i.e, one monitor for alfanumeric text, and one for graphics or images display. The software is developed at the International Institute for Aerospace Survey and Earth Sciences (ITC), Enschede, The Netherlands by a group of researchers lead by Prof. Allard Meijerink.. This particular version was released in March, 1992 with some new and improved facilities, e.g. the whole programs have been speed up, limitations on file size have been reduced or removed. Some cartographic map projections, and several new data formats e.g. TIFF file format are supported. The software is being used by many organizations ranging from private mapping company to research and training agencies. I have some experiences using the software for my post-graduate diploma image processing exercises. As far as image processing is concerned, I can say that ILWIS can handle most of the tasks, e.g. production of satellite image maps, 3-D visualization, etc., see the given example. The software is being used intensively by ITC reseachers and students as well as other geoinformation engineers around the globe. As a teaching tool, ILWIS deserves considerable praise for.providing tutorial disks and notes with some real case study datasets. The two-volume manual is very informative but poorly bind.